2020
DOI: 10.1186/s12879-020-4768-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of metallo-β-lactamase- producing carbapenem-resistant Enterobacter cloacae complex isolated in Heilongjiang Province of China

Abstract: Background: Enterobacter cloacae complex (ECC) is one of the most common extended-spectrum β-lactamase and carbapenemase-producing pathogen that threatens millions of the elderly and vulnerable sick persons. The objective of this study was to perform the molecular characteristics of the carbapenem-resistant E. cloacae complex (CREC) emerged in Heilongjiang Province of China. Methods: Six CREC strains were isolated from the patients with infectious diseases. The identities of ECC isolates were confirmed by sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…MLST analysis revealed diverse sequence types with ST93 as the predominant type followed by ST171 and ST145. ST93 was frequently reported in China, such as Hangzhou, Nanjing, Jiamusi, etc [17][18][19], whereas ST171 was commonly reported the U.S.A. and Japan [20,21]. The diversi cation of the sequence types of CREC in our hospital is consistent with previous studies which also showed genetic heterogeneity [22].…”
Section: Discussionsupporting
confidence: 89%
“…MLST analysis revealed diverse sequence types with ST93 as the predominant type followed by ST171 and ST145. ST93 was frequently reported in China, such as Hangzhou, Nanjing, Jiamusi, etc [17][18][19], whereas ST171 was commonly reported the U.S.A. and Japan [20,21]. The diversi cation of the sequence types of CREC in our hospital is consistent with previous studies which also showed genetic heterogeneity [22].…”
Section: Discussionsupporting
confidence: 89%
“…ST93 was frequently reported in China, such as Hangzhou, Nanjing, Jiamusi, etc. [ 18 20 ], whereas ST171 was commonly reported the U.S.A. and Japan [ 21 , 22 ]. The diversification of the sequence types of CREC in our hospital is consistent with previous studies which also showed genetic heterogeneity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,27,28 The dissemination of the ECC that produces KPC has been verified in China. 29,30 In addition, a previous study reported that 8.6% KPC-2-producing strains were detected in Chongqing. 31 However, our study showed that 12.4% (14/113) of the KPC-2-producing strains were found.…”
Section: Discussionmentioning
confidence: 98%